2014
DOI: 10.1179/1350503315z.00000000082
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Coastal Erosion on Archaeological Sites: A Case Study from Northern Ireland

Abstract: This paper will present research on the vulnerability mapping of coastal archaeological sites currently being undertaken in Northern Ireland. The ultimate aim of this research is improve current predictions of where archaeological sites and landscapes will be at risk in the future from coastal erosion. The initial stage of this approach uses a suite of oblique aerial photographs to construct a baseline of eroding locations and coastal geomorphology. The erosion baseline can then be integrated with existing his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Daire et al (2012) also developed a methodology to assess the vulnerability of archeological sites, taking into account various factors, such as distance from the cliff and exposure of the site to wave action, which Shi et al (2012) also applied to the Vilaine Estuary in Brittany, France. Work has also been undertaken in other areas to identify archeological sites at risk of SLR and associated coastal impacts, notably in the UK (Cook et al, 2019; Westley & McNeary, 2015), Italy (Anzidei et al, 2020), Newfoundland and Labrador (Pollard‐Belsheim et al, 2014; Westley et al, 2011), California (Reeder et al, 2010; Reeder‐Myers, 2015), Australia, and New Zealand (Bickler et al, 2013; Carmichael et al, 2017; Rowland, 1992).…”
Section: Impact From Changes In the Natural Physical Environment On Cultural Heritagementioning
confidence: 99%
“…Daire et al (2012) also developed a methodology to assess the vulnerability of archeological sites, taking into account various factors, such as distance from the cliff and exposure of the site to wave action, which Shi et al (2012) also applied to the Vilaine Estuary in Brittany, France. Work has also been undertaken in other areas to identify archeological sites at risk of SLR and associated coastal impacts, notably in the UK (Cook et al, 2019; Westley & McNeary, 2015), Italy (Anzidei et al, 2020), Newfoundland and Labrador (Pollard‐Belsheim et al, 2014; Westley et al, 2011), California (Reeder et al, 2010; Reeder‐Myers, 2015), Australia, and New Zealand (Bickler et al, 2013; Carmichael et al, 2017; Rowland, 1992).…”
Section: Impact From Changes In the Natural Physical Environment On Cultural Heritagementioning
confidence: 99%
“…There have been several studies on the vulnerability of archaeological heritage to erosion (e.g., recording threats to a standing stone or palaeosol, [6,7]). However, attempts to reconstruct the geomorphology around eroding sites have mostly looked at reconstructing sea level during lower or higher stages during prehistoric periods, or during the last few centuries from paintings or photographs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies assess the vulnerability of archaeological heritage to environmental processes (e.g. Daire et al 2012;Reeder et al 2012;Reeder-Myers et al 2015;Westley et al 2011;Westley and McNeary 2014). However, these studies base their VIs on historic or observed rates of environmental change, and therefore do not consider the ways in which climate change is predicted to alter current environmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of changes to temperature, precipitation patterns and wind were included inDaly's (2013) vulnerability assessment of SkelligMichael and Brú na Bóinne (see also Chadwick-Moore 2014;Grossi et al 2007;Westley et al 2011). In contrast, while acknowledging that climate change may increase the vulnerability of archaeological and heritage sites, several studies only based the VI on historic or observed rates of erosion or sea-level rise, rather than projected future change (e.g Daire et al 2012;Reeder et al 2012;Reeder-Myers et al 2015;Westley and McNeary 2014)…”
mentioning
confidence: 99%